Commodity revenues, agricultural sector and the magnitude of deindustrialization: A novel multisector perspective - Elkhan Sadik-Zada; Wilhelm Loewenstein; Yadulla Hasanli (Economies, 2019)
This study puts forward a model of a multisector economy and embeds it in a novel theoretical framework to address the relationship between commodity revenues and manufacturing output with a special focus on the role of the agricultural sector. The three-sector model lays the groundwork for analyzing policy choices in more complex sectoral settings. Based on the theoretical analysis, the study identifies the weight of the individual economic sectors in the public revenue generation as a determinant of the magnitude of rent seeking epitomized in the crowding out effect of investments in manufacturing. We find that enclave agriculture contributes to the deindustrialization pressure in the face of natural resource windfalls. The central finding of the multisector analysis is the conclusion that not diversification per se but rather a diversification with the substantial domestic factor or market orientation has the capability to limit the magnitude of deindustrialization. For the empirical validation of the theoretical findings, the study employs fixed effects, fully modified OLS, dynamic common correlated effects estimators and dynamic fixed effects estimators for the dataset of 113 developing and transition economies for 1963-2014 period. The estimations reveal that natural resource revenues correspond with a higher level of the manufacturing sector output. In the economies with a low level of economic diversification, commodity bonanza leads however to the shrinkage of the manufacturing. In the commodity revenue dependent settings, nevertheless, agricultural sector exports have a negative impact on the performance of the manufacturing sector. These findings are in line with the predictions of the theoretical model.
Keywords: C23; C32; D72; D73; L52; O41; 330; developing countries; economic diversification; enclave agriculture; multisector model; rent seeking